2021
DOI: 10.1111/jocs.15471
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative complications after cardiac surgery on long‐term survival

Abstract: Purpose The impact of postoperative complications on long‐term survival is not well characterized. We sought to study the prevalence of postoperative complications after cardiac surgery and their impact on long‐term survival. Methods Operative survivors (n = 26,221) who underwent coronary artery bypass grafting (CABG) (n = 13,054, 49.8%), valve surgery (n = 8667, 33.1%) or combined CABG and valve surgery (n = 4500, 17.2%) from 1993 to 2019 were included in the study. Records were reviewed for postoperative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0
31

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 35 publications
1
29
0
31
Order By: Relevance
“…2 Pahwa and colleagues further reported the impact of seventeen common post-operative complications and analyzed their impact on long-term survival. 3 The effect of multiple complications and various combinations of complications were also investigated and, understandably, the greater the number of complications, the worse was the survival. 2,3 The formulation of a risk stratification score based on post-operative complications following common cardiac surgical procedures may be used to estimate the likelihood of long-term survival for individual complications, as well as various permutations and combinations of complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Pahwa and colleagues further reported the impact of seventeen common post-operative complications and analyzed their impact on long-term survival. 3 The effect of multiple complications and various combinations of complications were also investigated and, understandably, the greater the number of complications, the worse was the survival. 2,3 The formulation of a risk stratification score based on post-operative complications following common cardiac surgical procedures may be used to estimate the likelihood of long-term survival for individual complications, as well as various permutations and combinations of complications.…”
mentioning
confidence: 99%
“…3 The effect of multiple complications and various combinations of complications were also investigated and, understandably, the greater the number of complications, the worse was the survival. 2,3 The formulation of a risk stratification score based on post-operative complications following common cardiac surgical procedures may be used to estimate the likelihood of long-term survival for individual complications, as well as various permutations and combinations of complications. This may have profound implications in devising strategies to prevent the most devastating combination of complications.…”
mentioning
confidence: 99%
“…Recently published data by Seese et al 2 reported the impact of the STS-defined major morbidities (prolonged ventilation, deep sternal wound infection, renal failure, reoperation, and stroke) on long-term outcomes. Pahwa et al 3 further reported the impact of 17 common postoperative complications and analyzed their impact on long-term survival. 3 The effect of multiple complications and various combinations of complications were also investigated and, understandably, the greater the number of complications, the worse was the survival.…”
mentioning
confidence: 99%
“…3 The effect of multiple complications and various combinations of complications were also investigated and, understandably, the greater the number of complications, the worse was the survival. 2,3 The formulation of a risk stratification score based on postoperative complications following common cardiac surgical procedures may be used to estimate the likelihood of long-term survival for individual complications, as well as various permutations and combinations of complications. This may have profound implications in devising strategies to prevent the most devastating combination of complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation